Positive feedback loop involving AMPK and CLYBL acetylation links metabolic rewiring and inflammatory responses - Wenke Wang; Boquan Wu; Mingjun Hao; Sichong Chen; Ruiting Cong; Wenjie Wu; Pengbo Wang; Qiaoyi Zhang; Pengyu Jia; Yuequn Song; Bo Liu; Siyao Qu; et al. (Cell Death and Disease)
Abstract Metabolic rewiring underlies effective macrophages defense to respond disease microenvironment. However, the underlying mechanisms driving metabolic rewiring to enhance macrophage effector functions remain unclear. Here, we demonstrated that the metabolic reprogramming in inflammatory macrophages depended on the acetylation of CLYBL, a citramalyl-CoA lyase, at lysine 154 (K154), and blocking CLYBL-K154 acetylation restricted the release of pro-inflammatory factors. Mechanistically, we found a crucial AMPK-CLYBL acetylation positive feedback loop, triggered by toll-like receptors (TLRs), involving AMPK hypophosphorylation and CLYBL hyperacetylation. The deacetylase enzyme SIRT2 acted as the bridge between AMPK phosphorylation and CLYBL acetylation, thereby regulating macrophage polarization and the release of pro-inflammatory cytokines. Furthermore, CLYBL hypoacetylation decreased monocyte infiltration, thereby alleviating cardiac remodeling. These findings suggest that the AMPK-CLYBL acetylation positive feedback loop serves as a metabolic switch driving inflammatory response and inhibiting CLYBL-K154 acetylation may offer a promising therapeutic strategy for inflammatory response-related disorders.